Regular infinite economies - Enrique Covarrubias (Banco de México, 2010)
The main contribution of this paper is to place smooth infinite economies in the setting of the equilibrium manifold and the natural projection map à la Balasko. We show that smooth infinite economies have an equilibrium set that has the structure of a Banach manifold and that the natural projection map is smooth. We define regular and critical economies, and regular and critical prices, and we show that the set of regular economies coincides with the set of economies whose excess demand function has only regular prices. Generic determinacy of equilibria follows as a by-product.
Keywords: D5; D50; D51; D80; D90; 330; General equilibrium; Infinite economies; Intertemporal choice; Uncertainty